Handbook on international trade policy - Gaisford, James D.; Kerr, William A. (Edward Elgar, 2007)
The Handbook on International Trade Policy is an insightful and comprehensive reference tool focusing on trade policy issues in the era of globalization. Each specially commissioned chapter deals with important international trade issues, discusses the current literature on the subject, and explores major controversies. The Handbook also directs the interested reader to further sources of information. The expert contributors cover both traditional and more current concerns including